The Problem of Separatism in Modern Spain: the Catalan Question - S. M. Gavrilova (Проблемы постсоветского пространства, 2022)
Catalan nationalism, rooted in the 19th century, transformed into separatism in the 1980s, threatening the existence of the Spanish state. The unstable political situation in the country caused by the crisis of the party system and serious economic problems is noticeably aggravated by the Catalan issue. The separatists representing the autonomy are not distinguished by unity, which provokes additional tension in the region, but they have a serious impact on the central government. The instability of the current Spanish government, formed by socialists, is compounded by the need to seek support from representatives of Catalan nationalist pariahs in the country’s parliament. This fact also makes it necessary for the ruling party not only to enter into a dialogue with the Catalan separatists, but also to agree to certain concessions.The situation is complicated by the fact that in the autonomy itself, the separatists are not supported by the majority of the population, and some residents of the region openly speak from unionist positions. The whole complex complex of contradictions of the Catalan question is critically connected with the problem of reforming the constitutional system of the Kingdom of Spain. The current Constitution of the country – which has become very obvious at the current stage of the development of the political and social crisis in Spain – requires a partial revision, primarily from the point of view of resolving the issue of the powers of a number of autonomies in the state and their interaction with the center.